Implementation of Power Point Learning Media at Alhadiriyah Vocational High School, East Jakarta - Suyuti; Marista Christia Shally (Formosa Journal of Science and Technology, 2022)
In order to optimize online learning, the use of learning media becomes a must used by every teacher in learning. Learning Media as a tool that serves as an intermediary or transmitter of message content in the form of visual and verbal knowledge information that can be used to stimulate the thoughts, feelings, attention and abilities or skills of students so as to encourage the learning process and learning. This study uses qualitative research methods, with a case study approach. The research Data was obtained through observation, interviews, and documentation with research subjects including teachers, students and parents in Sekolah menengah kejuruan alhadiriyah. This study uses triangulation of data from education experts, principals and vice curriculum. This research is important and interesting, because the topic is about the implementation of power point Learning media at alhadiriyah Vocational High School in East Jakarta, where schools use blended learning with offline and online systems to prevent the spread of Covid 19 in Indonesia, the number of which continues to increase.